PENGEMBANGAN E-MODUL PEMBELAJARAN IPA BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA - Putu Maretha Surya; Putu Dias Maretha Surya (Universitas Pendidikan Ganesha, 2021)
This study aimed to describe the characteristics, validity, practicality, and effectiveness of a product in form e-module of a guided inquiry-based science learning of eight grade students in the second semester of 2020/2021 academic year. The research method used is R&D with the development model modified from Thiagarajan (1973) from 4D to 3D which consists of stages define, design, and develop. The research design used a one-group pretest-posttest. The characteristics of the e-module in form of adding a feature live chat as an implementation of virtual inquiry learning. Data were analyzed quantitatively and qualitatively. The results show that: (1) The validity in terms of three aspects including material, media, and language on average were categorized as very valid, (2) Practicality in terms of teacher and students’ responses, respectively in the practical category, (3) The effectiveness in terms of posttest an average total score of 90.38 in the very good category and <g> = 0.82 in the high category. Based on these findings, it can be concluded that the e-module guided inquiry-based science learning developed is valid, practical, and effective in improving students' science process skills.